Ethnic identities, public spending and political regimes - Sugata Ghosh; Anirban Mitra (University of Kent, School of Economics, 2019)
Do democracies discriminate less against minorities as compared to non-democracies? How does the dominance of an ethnic group affect discrimination under various political regimes? We build a theory which tries to answer such questions. In our model, political leaders (democratically elected or not) decide on the allocation of spending on different types of public goods: a general public good and an ethnically-targetable public good which benefits the majority ethnic group while imposing a cost on the other minorities. We show that, under democracy, lower ethnic dominance leads to greater provision of the general public good while higher dominance implies higher provision of the ethnically-targetable good. Interestingly, the opposite relation obtains under dictatorship. This implies that political regime changes can favour or disfavour minorities based on the ambient level of ethnic dominance. Several historical events involving regime changes can be analysed within our framework and are consistent with our results.
Keywords: D72; D74; H40; 330; Ethnic identities; Discrimination; Public spending; Political regimes